Conscientious Objection - Triviño Caballero, Rosana (EUNOMÍA. Revista en Cultura de la Legalidad, 2018)
Abstract: Conscientious objection is an instrument to solve the conflict between legal and moral duties. In democratic societies, it is easy to find different features and nuances to define it which are not always compatible among them (i.e. conscientious objection as a legal right vs. objection as a conditioned exemption to the law accomplishment). Depending on the guiding notion, the potential advantages and disadvantages arisen from conscientious objection regulation can be identified. These aspects are the central points which articulate conscientious objection issues, which currently are mainly related to conflicts between professional duties and personal beliefs.